The Policy of Maximum Pressure on Iran. US Policy Objectives and Effects - Fiedler, Radosław (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2022)
The main goal of this paper is to examine the Trump administration’s maximum-pressure policy toward the Islamic Republic of Iran. The main causes and rationale for withdrawing from the nuclear JCPOA are identified. In addition, the consequences of maximum pressure are addressed, which harm the so far failed JCPOA restoration negotiations. An additional thread in the article is a critical appraisal of the sanctions policy, which for decades has failed to deliver the results expected by the USA, which is an inhibiting factor in a dynamically changing international environment. Moreover, the costs to the US of sanctions pressure on Iran have been identified.

Głównym celem artykułu jest analiza i ocena polityki maksymalnej presji administracji Trumpa wobec Islamskiej Republiki Iranu. Wskazano na główne przyczyny oraz uzasadnienie zwolenników maksymalnej presji przez administrację Trumpa po jednostronnym wycofaniu USA z nuklearnego porozumienia (JCPOA). Ponadto, omówiono skutki maksymalnej presji, które negatywnie wypływają na próby powrotu do JCPOA. Dodatkowym wątkiem w artykule jest krytyczna ocena polityki sankcji, która od dekad nie przynosi oczekiwanych przez USA skutków, co jest także czynnikiem hamującym w dynamicznie zmieniającym się środowisku międzynarodowym. Zidentyfikowano koszty, jakie ponoszą USA związane z presją sankcyjną wobec Iranu.
Polityka maksymalnej presji wobec Iranu. Cele i skutki polityki USA wobec Teheranu
Keywords: Iran; Trump; JCPOA; sanctions; maximum pressure; policy; nuclear program; Iran; Trump; JCPOA; sankcje; maksymalna presja; polityka; nuklearny program